Peran Pengadilan Tata Usaha Negara (PTUN) Surabaya dalam melaksanakan eksekusi berkekuatan hukum tetap - Hilmy, Gustian Hafizh (Maliki Interdisciplinary Journal, 2023)
Execution is the implementation of a court decision that has permanent legal force. In Article 116 of Law No. 5 of 1986, paragraphs (1), (2), and (3) explain that every TUN official who loses in a trial must carry out the contents of the court decision. If the losing party does not carry out the results of the decision, then the winning party may submit a request for execution to TUN court, and if the results of the decision have not been implemented, the head of the court can submit this matter to his superior agency according to his position level, and if the results of the decision are still not implemented, the head of the court submits this matter to the president as the holder of the highest government power to order the official to carry out the verdict. As explained in articles (4), (5), and (6). From the results of this research, readers can find out the role of the State Administrative Court (PTUN) in ensuring the implementation of court decisions, the importance of effective implementation in maintaining the rule of law and administrative justice, and challenges and deficiencies in the implementation of court decisions, including the lack of legal regulation and compliance problems by government officials. The author suggests that a clean and strong government can be achieved by increasing the functionality and performance of the government system.